Study of Monoamine Oxidase-B and Indole Derivatives Using Two Molecular Docking Programs: Molegro and MOE - Soufi, W.; Merad, M.; Hacene, F. BOUKLI; Ghalem, S. (International Journal of Scientific Research and Management (IJSRM), 2020)
Inhibition of the enzyme Monoamine oxidase (MAO) is an important approach in the treatment of Parkinson’s disease. A series of indole derivatives were synthesised and evaluated as inhibitors of MAO-B may give insight to develop new ways of antiparkinson drug, In general, the derivatives were found to be selective MAO-B inhibitors with IC50 values . MAO-B inhibitors,  are considered useful in the therapy of Parkinson’s disease since oxidation by MAO-B represents a major catabolic pathway of dopamine in the central nervous system .                     Our goal of research is to study the inhibition of MAO-B by molecular modeling methods. Different molecular modeling tools are used to perform this work (molecular mechanics, molecular dynamics and molecular docking by two programms MDV ( molegro virtual docker) and MOE (modelling Opering Environment. The results obtained from this work, into which the inhibition of MAO-B by molecular modeling methods was elucidated, allow us to conclude that indole derivatives are promising reversible MAO-B inhibitors with a possible role in the treatment of neurodegenerative diseases such as Parkinson’s disease (PD).